Antimicrobial activity of some plants extracts on bacteria isolated from acne vulgaris patients - Rasool, Khetam H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Background: Acne is a cutaneous pleomorphic disorder skin disease most frequently occurring during the adolescent in ages of 12-24, with estimated percentage ( 85%) . There are different ways to treat acne such as using of antibiotics , herpes , and mixing treatments . Methods : Antibacterial activity of four concentrations (100,50,25,12.5)mg /ml of alcoholic and cold aqueous crude extracts of Cinnamon(Cinnamomum verum ), Henna (Lawsonia inermis ) , Lupine (Lupinus luteus) were studied against aerobic and an aerobic bacteria isolated from inflamed and discharging pus from thirty Iraqi acne vulgaris patients refer to dermatology unit at AL-Kindy Hospital from December 2016 to March 2017.All information (age, sex ,diseases and using topical treatments) were recorded .The bacterial isolates were identify using morphological characteristics, biochemical tests and the Vitek-2 compact system. Results: Among (30 )Acne samples taken, 8 (26.7%) samples were from males age range (19-33) years and 22(73.3%) were from females within age (17-29)years . twenty five (83%) samples were culture positive, and only (17%) of samples revealed no growth .Most frequent bacteria which isolated (aerobically) from acne patients were Staphylococcus aureus ( 60%), Staphylococcus epidermidis (20%), Escherichia coli (8% ), Pseudomonas aeruginosa (4%), and an aerobic bacterial isolates were Propionibacterium acnes (8%) isolates. Antibiotic sensitivity tests were performed against, Ampicillin, Clindamycin, Gentamicin, Cotrimoxazole, Erythromycin, Vancomicine, Tetracycline, Doxycycline, and Azithromycin.All bacterial isolates were resistance to Ampicillin. Staphylococcus aureus and S. epidermidis were sensitive (100%) to Doxycycline and Azithromycin, P. acne were also highly sensitive to these two antibiotics (95.5%,97.1%) respectively, while E. coli and P. aeruginosa were (100%) resistance to these antibiotics. Gentamicin and tetracycline were susceptible by most of the study isolates except for P. aeruginosa which was very resistance to CN and TE (100%&94.8%) respectively. The antimicrobial potential of cold water and alcoholic crude extracts of Cinnamon (Cinnamomum verum ), Hinna (Lawsonia inermis), and Lupine (Lupinus luteus), in concentrations (100,50,25,12.5) mg/ml against the gram positive and gram negative isolates were tested through a well-diffusion method. Alcoholic extract of Henna leaves in concentration (100mg/ml) showed high inhibitory activity to all isolates compared with the aqueous extract and the all concentration of cinnamon aqueous and alcoholic extracts ,while lupine extracts had no effect on all bacterial isolates . Conclusion: Gram-positive bacteria were the most common microorganisms involved in acne infection. There are variations in the incidence of acne infection in relation to sex, age; Alcoholic extract of the Henna leaves could be used to treat acne.